Livelihood, cash Transfer, and graduation approaches: How do they compare in terms of cost, impact, and targeting? - Sulaiman, Munshi (International Food Policy Research Institute (IFPRI), 2022)
This book chapter was published in the book named Boosting growth to end hunger by 2025: The role of social protection and the definite version is available at : https://ebrary.ifpri.org/utils/getfile/collection/p15738coll2/id/132858/filename/133064.pdf